2018
DOI: 10.1002/lary.27320
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Obstruction Site Observed With Drug‐Induced Sleep Endoscopy in Patients With Obstructive Sleep Apnea

Abstract: Objective To perform a meta‐analysis on the distribution and characteristics of the obstructive site in patients with obstructive sleep apnea (OSA) using data from a variety of published studies that evaluated the obstruction with drug‐induced sleep endoscopy (DISE). Methods A literature search was performed to identify studies in which DISE was used to identify the obstruction site in adult patients with OSA, and the obstruction site was described in sufficient detail. Four items were evaluated in the meta‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
(159 reference statements)
0
20
0
2
Order By: Relevance
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
“…21 Lee and Cho presented a meta-analysis (most studies used qualitative classification with heterogeneity) and found that the upper airway usually had multilevel rather than single-level obstructions; furthermore, they reported that the soft palate was the most common obstructive site and that the tongue base was obstructed in half of the patients. 22 They also stated that the rate of an obstruction ≥75% (defined as significant obstruction) was 69.3% for the soft palate and 56.8% for the tongue base, indicating that significant obstructions occurred at these 2 levels. As compared with our study, the rate of significant obstruction was 56% for the RP level, 55% for the oropharyngeal level, 15% for the RG level, and 33% for the RE level.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing number of investigators have advocated drug‐induced sedated endoscopy (DISE) as a method to evaluate the site of obstruction in OSA (Dijemeni, D'Amone, & Gbati, 2017; Yalamanchili et al., 2019). Lee and Cho (2019) reviewed the obstruction site observed with DISE by using the four‐level classification system in patients with OSA. They reported a highly variable rate of obstruction for the tongue base, ranging from 4% to 88%, with an average tongue obstruction rate of 51.6%.…”
Section: Discussionmentioning
confidence: 99%